Finding One's Footing When Everyone Has an Opinion. Negotiating an Acceptable Identity After Sexual Assault - Dundas, Ingrid; Mæhle, Elin; Stige, Signe Hjelen (Frontiers in Psychology, 2021)
Identities used to describe oneself after trauma may influence recovery, and searches for acceptable identities after sexual assault can be challenging. Fifteen Norwegian female survivors of sexual assault were recruited at a clinical center, and were individually interviewed about post-assault discussions with others. Our focus was on the experiences of non-blaming and believing interactions with others, and how these interactions can be understood as a process of searching for acceptable identities after sexual assault. A reflexive thematic analysis resulted in four themes: navigating between other people’s stories and one’s own; realizing the seriousness of the assault without drowning in the upset of others; finding a place between too much closeness and too much distance; and being more than a victim. We discuss the importance of participants retaining agency in post-assault interactions. We suggest that being a survivor of sexual assault increases the probability, even in believing and non-blaming interactions, of being cast in a subject–object relationship with less freedom and agency than before. Navigating toward acceptable identities may mean working one’s way back to being a subject in a subject–subject relationship again.